TEKNIK DAN KOMUNIKASI PEMASARAN YANG TERINTEGRASI MENGGUNAKAN PENDEKATAN DARI INTERFACE MARKETING-FINANCE PADA PRODUK LIFEBUOY DI PT. UNILEVER INDONESIA TBK. - Ibnu Wardani (Jurnal Akuntansi dan Pajak, 2022)
The finance and marketing divisions have a fairly high degree of independence, but on the other hand, the two divisions must work together to get good performance. So there needs to be a decision to integrate the finance and marketing divisions because the two divisions will always be in touch and can provide value to the company. An adaptive integration is needed to be able to follow the rhythm and dynamics of the international market. The basics of integration between the finance and marketing divisions have not changed radically with the need to pay attention to the marketing-finance interface. The marketing-finance interface technique is a method that has been used by all global industries, including the Fast Moving Consumer Goods (FMCG) industry which has many brand variants, due to competition for similar products to earn profits. This study aims to analyze and create an alternative with the marketing-finance interface at PT Unilever Indonesia Tbk. The research data consisted of primary and secondary data. Primary data was obtained through interviews with company management and with one of the lecturers at Diponegoro University who has experience in the Fast Moving Consumer Goods (FMCG) industry so that the data source can provide complete data accuracy. Then the secondary data in this study comes from the annual report data obtained from the company PT. Unilever. The research method used is a qualitative method with depth interviews, so this research can provide a detailed description of the research object. The research data were analyzed using the Miles and Huberman method including data reduction, data presentation and conclusion drawing. The results of the study state that a person's consumption level will continue to experience growth where the level of public consumption in Indonesia has a fairly high potential. Consumer behavior in choosing a product can be influenced by several factors, namely internal factors and external factors. Indonesia itself has such a large market. With Lifebuoy's strong position in the soap industry, it gives Lifebuoy an advantage to further strengthen its market share. In addition, at Unilever Indonesia, the relationship between the marketing division and the finance division has been well established as a cultural adaptation in accordance with the FMCG industry. Communication accompanied by a good understanding in terms of strategy formulation from the marketing and financial divisions will improve the company's financial performance. In overcoming competition in the FMCG industry, especially in the soap category, Unilever Indonesia has the right strategy in order to win the competition in Indonesia and in the world. Lifebuoy, which is Unilever's flagship product, will continue to maintain its advantages and continue to look for opportunities to continue to grow through product innovation.